Review article: Paracrine effects of Transplanted Neural stem cells in Ischemic strokes - Methaq Mueen Al-Kaabi; Abdal-jabbar Falih AL-Rubai (Iraqi Journal of Cancer and Medical Genetics, 2021)
Ischemic stroke is one of the most common causes of death in the world. Pathophysiologically, ischemic stroke is associated with blood brain barrier disruption, cell loss, inflammation and intense immune reaction which worsen the condition. The Stroke Treatment Academic Industry Roundtable recommends the use of any treatment that has multiple mechanisms of action to restore the neurological function. Growing evidences from researchers to understand the biology of neural stem cells indicated that these cells have crucial role in brain homeostasis and have high therapeutic potential to modify and restore neurological function after neurovascular injury. Contemporarily, Paracrine hypothesis is growing and indicated that neural stem cells transplantation can release several neurotrophic factors which can regenerate, restore, and modulate the neurological diseases by mitigating the inflammatory process, reducing the immune reactions and also can stimulate the angiogenesis and neurogenesis. This, generate a new attitude toward the development of acellular therapy instead of using whole allogenic neural stem cells in the regenerative medicine. This review is to focus on the paracrine effects of transplanted neural stem cells in the brain ischemic injuries which can modulate and improve the neurological outcome after ischemic injury.